Acute myocardial infarction due to coronary artery embolus associated with atrial fibrillation. (December 2013) - Xu, Bo; Williams, Paul; Burns, Andrew T.
Abstract Coronary artery embolus is a rare and potentially under- recognised cause of acute myocardial infarction. We describe the case of an 80-year-old woman presenting with an acute coronary syndrome secondary to coronary artery embolus associated with atrial fibrillation, which was successfully treated with the use of a thrombectomy aspiration catheter.